2017
DOI: 10.1016/j.scriptamat.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Novel micro-flat springs using the superior elastic properties of metallic glass foils

Abstract: A thin metallic glass foil of 100 mg massforming a sinusoidal arc behaves as nonconventional flat micro-spring withstanding loads 10 5 times higher than its load. Upon a normal load applied on the top of the arc, the foil deforms elastically leading to sinusoidal wavy patterns of higher order. The lifespan of the novel spring is higher than conventional low cycle springs and can potentially be further improved by eliminating surface and edge preparation induced defects. This unique behaviour of metallic glass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Recently, Aljerf et al [14] have shown the thermomechanical wavy shaping of vitrified ribbon without thermal embrittlement. In our recent work [15], we experimentally showed the possible use of the reversible wavy elastic response as a novel micro-flat-spring.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Aljerf et al [14] have shown the thermomechanical wavy shaping of vitrified ribbon without thermal embrittlement. In our recent work [15], we experimentally showed the possible use of the reversible wavy elastic response as a novel micro-flat-spring.…”
Section: Introductionmentioning
confidence: 99%